الحاجات الإرشادية لدى تلاميذ الرابعة متوسط - عتير، مباركة, لطيف، مباركة (جامعة الوادي university of Eloued, 2022)
الملخص: هدفت الدراسة إلى معرفة طبيعة الحاجات الإرشادية لتلاميذ السنة الرابعة متوسط ومعرفة حاجاتهم التربوية والاجتماعية والانفعالية والجسمية وقد تحددت الدراسة بالمنهج الوصفي المعتمد على الاستكشاف الملائم لطبيعة دراستنا وقد اختيرت العينة بطريقة العشوائية البسيطة من متوسطة مبارك بوضبية بدائرة الرقيبة ولاية الوادي وقد شملت الدراسة (70) تلميذ وتلميذة. تمت معالجة البيانات باستعمال المتوسط الحسابي والنسب المئوية أما أداة القياس تمثلت في مقياس الحاجات الإرشادية، وأسفرت نتائج الدراسة على مجموعة من الحاجات الإرشادية وهي بترتيب من أكثر أهمية إلى اقل أهمية وهي: -الحاجة إلى مكتبة للمطالعة. -الحاجة إلى تقليص الحجم الساعي. -الحاجة ممارسة الرياضة للبنات. -الحاجة لمصلى داخل المؤسسة. -الحاجة لتوفير الانترنت. Abstract The study aimed at knowing the nature of the counseling needs of the fourth-year intermediate students and knowing their educational, social, emotional and physical needs. The study was determined by the descriptive approach based on the appropriate exploration of the nature of our study. The sample was chosen in a simple random manner from the Mebarek Boudhabia Intermediate School in the Reguiba Department of the Valley State. The study included (70) male and female students. The data were processed using the arithmetic mean and percentages, and the measuring tool was the indicative needs scale. The results of the study resulted in a set of guiding needs, the most important of which are the following: - The need for a reading library. - The need to reduce the courier size. - The need to exercise for girls. - The need for a chapel inside the institution. - The need to provide the Internet.
دراسة ميدانية في متوسطة شهيد مبارك بوضبية
مذكرة ماستر علوم التربية تخصص إرشاد وتوجيه
Keywords: الجاجات الإرشادية، الإرشاد النفسي; Consultation, consultation psychologique; Counseling, psychological counseling